A Study of Embracing Adolescent Islamic Moral Values at Two Schools in Rural Area - Nuriman, Nuriman; Mahmoud, Essra; Hamzah, Aswati Bt.; Yusnaini, Yusnaini (SCAD Independent, 2024)
Adolescent behaviour that embraces a lifestyle incongruous with Islamic moral values in the micro-social environment may impede the nation's development in the future. This phenomenon has emerged as a crucial and pressing issue in adopting Islamic moral values among adolescents. This research endeavored to gauge the impact and correlation of adhering to Islamic moral vertical and horizontal values on adolescent behaviour. The study also indicated variations in adopting vertical and horizontal moral principles among male and female adolescents. The research centred on senior high school students residing in rural regions of the North District in Aceh province. Three hypotheses were formulated and analyzed through IMB-SPSS.22.0. Data from 136 students aged between 16-19 years were processed using instruments sourced from the Muslim Personality-Religiosity Inventory (MPRI), which comprised twenty indicators, and t-tests and r2 were conducted. The research indicated a significant correlation and Influence between Islamic moral vertical and horizontal values and adolescent behavior. Furthermore, the study discovered that male and female students embrace vertical and horizontal moral values differently at a significant level. This finding confirmed that adopting Islamic moral values shapes students' conduct. Therefore, all adolescents must embrace Islamic moral values as they engage in their communities.